2016
DOI: 10.2135/cropsci2015.06.0394
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Temporal Variation in Soybean Seed Protein and Oil across the United States

Abstract: Soybean [Glycine max (L.) Merr.] seed composition data are becoming critical for efficient marketing and trade of soybean and soybean products. Previous reports of variation in seed protein and oil across regions within the United States focused on variation associated with state and regional boundaries. We conducted an analysis of an 8‐yr survey of seed protein and oil across US states and regions, including a geostatistical approach to better characterize the continuous variation in seed composition on a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 47 publications
(74 reference statements)
5
46
1
Order By: Relevance
“…Rotundo, Miller‐Garvin, and Naeve (2016) identified a moderate regional dependency in soybean seed composition with a minimum range of about 300 km. Similarly, in a comprehensive review, Hu and Wiatrak (2012) concluded that the combined effects of planting date, photoperiod, temperature, and precipitation are primary factors influencing soybean seed yield and quality (Hu & Wiatrak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rotundo, Miller‐Garvin, and Naeve (2016) identified a moderate regional dependency in soybean seed composition with a minimum range of about 300 km. Similarly, in a comprehensive review, Hu and Wiatrak (2012) concluded that the combined effects of planting date, photoperiod, temperature, and precipitation are primary factors influencing soybean seed yield and quality (Hu & Wiatrak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Helms and Orf (1998) showed that traditional breeding efforts could increase protein by 5 to 7%, but this simultaneously decreased yield by 70 to 110 kg ha -1 resulting in an overall decrease in protein ha -1 . The effect of the production location has possibly the greatest influence on seed yield, where soybean grown in the northern Corn Belt is consistently lower in protein compared to those grown in southern states (Rotundo et al, 2016). Hurburgh et al (1990) found that soybean from northern states contained 1.5 to 2% less protein and 0.2 to 0.5% more oil than soybean produced in the South and southeastern United States.…”
mentioning
confidence: 99%
“…Significant spatial and temporal variability exists for protein and oil (Brumm and Hurburgh, 2006). Rotundo et al (2016) determined that the spatial variation occurs at scales lower than politically defined regional and state lines. Many underlying weather and environmental factors have been suggested to explain this variation, including differences in temperature throughout the growing season (Gibson and Mullen, 1996;Howell and Cartter, 1958;Thomas et al, 2003;Wilson, 2004;Wolf et al, 1982;Yaklich and Vinyard, 2004).…”
mentioning
confidence: 99%
“…There exists considerable variation in soybean protein concentration, based on a number of factors including genetics (Serretti et al, 1994;Zarkadas et al, 1999Zarkadas et al, , 2007 and environmental conditions (Rotundo et al, 2016), at the local, regional, and international levels (Thakur and Hurburgh, 2007;Karr-Lilienthal et al, 2004;Medic et al, 2014;Naeve, unpublished data, 2015). Studies like these, as well as soybean quality surveys, report changes in amino acids resulting from protein concentration differences across a number of locations, genotypes, and in some cases, years.…”
mentioning
confidence: 99%